2018
DOI: 10.1097/inf.0000000000001900
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic Manifestations of Brucellosis in Children

Abstract: Brucellosis is commonly presented with cytopenia, especially in bacteremic episodes with fever. However, pancytopenia is uncommon and its finding should alert the physician to look for other possible etiologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 23 publications
2
17
0
2
Order By: Relevance
“…However, Hb, ESR and Ferritin only changed in osteoarticular involvement group and there was no difference between group without osteoarticular involvement and control group. The ROC analysis revealed that NEU, CRP and ALT may have a complementary role in the differential diagnosis of childhood brucellosis.These abnormal laboratory findings were accordance with the results of other studies (29)(30)(31). Clinical and laboratory characteristics of pediatric brucellosis patients with osteoarticular involvement are differ from cases without skeletal complications.…”
Section: Accepted Manuscriptsupporting
confidence: 91%
“…However, Hb, ESR and Ferritin only changed in osteoarticular involvement group and there was no difference between group without osteoarticular involvement and control group. The ROC analysis revealed that NEU, CRP and ALT may have a complementary role in the differential diagnosis of childhood brucellosis.These abnormal laboratory findings were accordance with the results of other studies (29)(30)(31). Clinical and laboratory characteristics of pediatric brucellosis patients with osteoarticular involvement are differ from cases without skeletal complications.…”
Section: Accepted Manuscriptsupporting
confidence: 91%
“…1 The incidence of anemia has been reported as 13.3%-55% in different pediatric series. 1,12,[18][19][20] In the present study anemia was the most common hemeatologic finding of brucellosis. We used hemoglobin levels determined for age to be able to make an objective evaluation when describing hematological findings like most other studies.…”
Section: Brusellosis In Pediatric Patients May Have a Wide Variety Of...mentioning
confidence: 85%
“…Authors thought that, this difference may be a result of choosing relatively low cut-off for hemoglobin levels of 10 mg/dl in order to minimize the anemia cases misrelated to brucellosis. 18 Moderate to severe leukopenia and thrombocytopenia as well as normal leukocyte and thrombocyte counts in patients with brucellosis were reported. 1,12,18,19,21 On the contrary of leukopenia predominance in previous reports, in a prospective case-control study including 100 brucellosis patients and 100 healthy individuals, the authors found that WBC, CRP and neutrophil counts were significantly higher in the brucellosis group.…”
Section: Brusellosis In Pediatric Patients May Have a Wide Variety Of...mentioning
confidence: 99%
See 1 more Smart Citation
“…Brucellosis also produces a variety of hematologic complications abnormalities in hematological parameters, including mild anemia, leukopenia, thrombocytopenia, or pancytopenia, which can be confused with hematological disease [16]. Mild anemia and leukopenia are frequent in brucellosis, whereas severe thrombocytopenia and pancytopenia are less frequently observed [17]. Therefore, brucellosis is frequently misdiagnosed as a primary hematologic disease or malignancy.…”
Section: Discussionmentioning
confidence: 99%